Mesoporous Magnesium Oxide Adsorbent Prepared via Lime (Citrus aurantifolia) Peel Bio-templating for CO2 Capture - A. H. Ruhaimi; C. C. Teh; Muhammad Arif Ab Aziz (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
The utilization of the lime (Citrus aurantifolia) peel as a template can improve the adsorbent’s structural properties, which consequently affect its CO2 uptake capacity. Herein, a mesoporous magnesium oxide (MgO-lime (Citrus aurantifolia) peel template (LPT)) adsorbent was synthesized using an LPT. MgO-LPT demonstrated improved structural properties and excellent CO2 uptake capacity. Moreover, another MgO adsorbent was prepared via thermal decomposition (MgO-TD) for comparison. The prepared adsorbents were characterized by N2 physisorption, Fourier transform infrared spectroscopy and thermogravimetric analysis. The CO2 uptake of these adsorbents was under 100% CO2 gas and ambient temperature and pressure conditions. MgO-LPT exhibited a higher Brunauer–Emmett–Teller surface area, Barrett–Joyner–Halenda pore volume, and pore diameter of 23 m2.g−1, 0.142 cm3.g−1, and 24.6 nm, respectively, than those of MgO-TD, which indicated the mesoporous structure of MgO-LPT. The CO2 uptake capacity of MgO-LPT is 3.79 mmol CO2.g−1, which is 15 times that of MgO-TD. This study shows that the application of lime peel as a template for the synthesis of MgO adsorbents is a promising approach to achieve MgO adsorbents with enhanced surface area and thus increased CO2 capture performance. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).